ngữ pháp tiếng Anh trình độ trung cấp = Fundamental of English grammar - Azar, Betty Schrampfer; Nguyễn Thành Yến (Tp.HCM : Nxb Tp.HCM, 2003)
Present and past; Present perfect and past; Future; Modals...
Keywords: Anh ngữ; English language; Anh ngữ -- Ngữ pháp; English language -- Grammar